Corporate governance and declining firms performance - Evans, John; Evans, Robert; Loh, S. (Edith Cowan University, 2002)
This research investigates the relationship between corporate governance structuresand the decline in firm performance in a sample of Australian firms. Firmsexperiencing extended periods of financial decline are expected to react to this declineby instigating governance related changes. In particular, the relationship betweendeclining firm performance and executive compensation, board composition, boardmeeting frequency and insider share ownership is examined.Contrary to the hypothesised relationship, firms in decline did not generally reactthrough changes to insider ownership levels, numbers of outside directors and CEOpay levels. Firms did, however, respond to poor performance by significantlyincreasing board meeting frequency.